A prospective study about the discrepancy between postmortem inspections conducted by emergency physicians and forensic pathologists. (July 2020) - Lim, Ji Yeon; Jung, Koo Young; Lee, Duk Hee; Yang, Kyung-moo; Choi, Minsung; Park, Jong-Pil; Lee, Jae Hee
Abstract: Background: In South Korea, most postmortem examination certificates (death certificates) are issued by attending physicians working in the emergency department (ED). However, ED overcrowding has made continuous education and quality control of the postmortem examination certificate difficult. In this context, the National Forensic Service (NFS) is conducting an on-site postmortem inspection (OPI) project. Aims: In this study, we analyzed the discrepancy between postmortem inspection conducted by emergency physicians and forensic pathologists and identified the effects of the OPI project. Method: The study examined cases where OPIs were conducted by NFS medical examiners (forensic pathologists) on patients who died on arrival or died in the ED where the OPI project is being conducted. The case reports written by emergency physicians were compared with the postmortem examination certificates written by medical examiners to analyze the discrepancy in cause and manner of death between the two groups. Result: A total of 75 field examinations were conducted during the study period, with a 56% agreement rate between the two groups regarding cause of death. Manner of death was consistent at 73.3% and the most common reason for requesting an OPI was that the cause of death was presumed to be natural, but what that cause may be was unclear. Conclusion: The discrepancy in postmortem examinations between emergency physicians and medical examiners is attributed to various factors. To ensure more reliable postmortem examinations, emphasis should be placed on improving the death investigation system and quality control activities for physicians. Highlights: Postmortem inspection by emergency physicians and forensic pathologists was compared. Cause of death was consistent at 56% in both groups. Manner of death was consistent at 73.3% in both groups. Improving the death investigation system and quality control is important.